Prediction of family resilience based on marital commitment and psychological capital in married couples of Takab city - Ehsani, Hosseinali; Shahriari, Mansure; Zare Bahram Abadi, Mehdi; Izadi, Mahshid (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: In the happiest marital relationships, people sometimes face stressful situations or problems, and yet, their relationships can remain stable. In this context, it is thought that determining which resources provide relational resilience can provide guidance for strengthening a marital relationship; Therefore, the current research was formed with the aim of predicting family resilience based on marital commitment and psychological capital. Methods: The current research is descriptive of the correlation type; For this purpose, a random sample of 296 people was selected from the statistical population of married men and women in Takab (from West Azarbaijan province). In this research, in order to collect data, McCubbin et al.'s family resilience questionnaire (1986), Stanley and Markman's Marital Commitment Questionnaire (1992), and Luthans' Psychological Capital Questionnaire (2007) were used. The data obtained from the research were analyzed with SPSS-23 software. Results: The results of multivariate regression showed that marital commitment can predict family resilience with 99% confidence and among the components of psychological capital, self-efficacy can predict family resilience with 95% confidence. Conclusion: As a result, in order to face and deal with problems and crises, it is emphasized on preserving family unity and marital commitment and psychological capital.